Adsorption of Cd and Mn from neutral mine effluents using bentonite, zeolite, and stabilized dewatered sludge - Veronika Prepilková; Juraj Poništ; Anna Ďuricová; Jozef Salva; Marián Schwarz; Dagmar Samešová; Martina Mordačová (Environmental Sciences Europe, 2024)
Abstract This study aimed to investigate the adsorption efficiency of Cd and Mn using natural sorbents—bentonite, zeolite and stabilized digested dewatered waste sludge. The main contributions of the scientific article are in adding to the scientific knowledge of the use of natural and waste sorbents in the removal of heavy metals from neutral mine effluents. Current studies mainly focus on metal removal by sorption using natural sorbents from acid mine drainage. This study investigates sorption in neutral mine drainage. The efficiency of the sorption process was evaluated using the following parameters: efficiency (%) of metal ion removal, Freudlich and Langmuir adsorption isotherm constant. The AES–ICP method (atomic emission spectrometry with inductively coupled plasma) was used for the initial metal analysis of the materials used. The atomic absorption spectrometry (AAS) method was used for the analysis of Cd and Mn in the sorption process. The maximum efficiency of Mn removal by bentonite at the end of the test was approximately 90%. The removal of Mn by zeolite was considerably lower—about 20% compared to the use of sludge—80%. Based on the sorption efficiency, the sludge was suitable for sorption. Much higher levels of Cd sorption were achieved using sludge compared to using natural bentonite and zeolite. The main novelty of the work lies in the sorption of metals using dewatered digested sludge. Previous studies have focused on metal sorption using activated sludge. Most previous studies focused on sorption from acid mine drainage. The novelty of this study is that we focused on the sorption of neutral mine drainages, which are typical for the location we are monitoring.